Global implications of the renminbi's ascendance - Eswar Prasad (Asian Development Bank Institute (ADBI), 2014)
This paper evaluates the prospects for the renminbi's role as an international currency and the implications for global financial markets. Although the People's Republic of China (PRC) does not have either an open capital account or a flexible exchange rate, the renminbi has attained considerable traction as an international currency on account of the PRC's rising shares of global trade and gross domestic product. Through bilateral swaps that the People's Bank of China has established with other countries' central banks, the renminbi is also becoming more prominent in international finance. However, the renminbi is unlikely to become a major reserve currency in the absence of capital account convertibility, a flexible exchange rate, and better-developed financial markets. The renminbi's rising prominence - if it is accompanied by significant economic reforms within the PRC - could add to the stability of Asian and global financial systems.
Keywords: F3; F4; E5; 330; renminbi internationalization; reserve currency; capital account convertibility; exchange rate flexibility; currency swaps